Discovery of atmospheric-wind-driven electric currents in Saturn's magnetosphere in the gap between Saturn and its rings - Khurana,KK; Dougherty,MK; Provan,G; Hunt,GJ; Kivelson,MG; Cowley,SWH; Southwood,DJ; Russell,CT (Geophysical Research Letters, 2018)
Magnetic field observations obtained by the Cassini spacecraft as it traversed regions inside of Saturn's D ring packed a genuine surprise. The azimuthal component of the magnetic field recorded a consistent positive perturbation with a strength of 15–25 nT near closest approach. The closest approaches were near the equatorial plane of Saturn and were distributed narrowly around local noon and brought the spacecraft to within 2,550 km of Saturn's cloud tops. Modeling of this perturbation shows that it is not of internal origin but is produced by external currents that couple the lowlatitude northern ionosphere to the lowlatitude southern ionosphere. The azimuthal perturbations diminish at higher latitudes on field lines that connect to Saturn's icy rings. The sense of the current system suggests that the southern feet of the field lines in the ionosphere leads their northern counterparts. We show that the observed field perturbations are consistent with a fieldaligned current whose strength is ~1 MA/radian, that is, comparable in strength to the planetaryperiodoscillationrelated current systems observed in the auroral zone. We show that the Lorentz force in the ionosphere extracts momentum from the faster moving lowlatitude zonal belt and delivers it to the northern ionosphere. We further show that the electric current is generated when the two ends of a field line are embedded in zonal flows with differing wind speeds in the lowlatitude thermosphere. The windgenerated currents dissipate 2 × 1011W of thermal power, similar to the input from the solar extreme ultraviolet flux in this region.